(untitled) - Penza, Pietro (Canada, 2001)
First, it takes a decidedly global approach–an essential ingredient for any comprehensive work on market risk. Second, it ties the scientifically grounded, yet intuitively appealing, VaR measure to earlier, more idiosyncratic measures of market risk that are used in specific market environs (e.g., duration in fixed income). Finally, it encompasses all of the accepted approaches to calculating a VaR measure and presents them in a clearly explained fashion with supporting illustrations and completely worked-out examples.
Keywords: Financial futures,Risk management,Tài chính tương lai,Quản lí rủi ro